Partisipasi Orang Dewasa Terhadap Kecakapan Baca Pada Siswa Lambat Baca di Sekolah Dasar - michelle andhi aprilyne, michelle andhi (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2024)
Technology that becomes more advanced has an impact on the field of education where books are no longer needed. Anyone can access information through a device. Information is obtained through reading literacy skills. Facts show that there are still some students who are not fluent in their ability to read. Literacy skills are difficult to achieve if the students do not yet have good skills in reading as it is a basic step in human life. This research was conducted using descriptive qualitative research methods which explained the topic of the problem in detail. It applied observation, interview, and documentation techniques that produced triangulation data, which were analyzed using triangulation and Miles’ method. The results showed that adult participation in the reading skills of slow-reading students had a very positive impact, where the students who were still confused to read letters in the first place, finally be able to read word for word to a composed sentence. Adult participation in slow-reading students also improves interest and motivation in the learning process